Answer: (-16, 40)
Step-by-step explanation: Using substitution, you can but the first y=-4x-24 into the second equation y+2x=8. So, you take what y is (which is -4x-24) and substitute it for the second y in the equation y+2x=8.
Your equation should now look like this (-4x-24) + 2x = 8.
You can then solve -4x -24 +2x =8. Combine like-terms (-4x+2x) to get -2x-24=8. Then use inverse operations and add 24 from both sides (so from the -2x-24 side and 8 side). This will then give you -2x=32. divide both sides from -2x to get:
x = -16
Then, plug in x= -16 into the first equation (y= -4 (-16) - 24). Then use PEMDAS and multiply -4 and -16 to get +64. Subtract 24 to get:
y = 40